The method of Imam Al-Damiry (D. 808 AH) in Al-Jarh and Al-Ta’deel through his book Al-Najm Al-Wahaj fi explain Al-Minhaj - Al-Lahabi, Abdulsalam Hezam Musaed (Journal of Islamic Sciences, 2023)
This research aims to study the method of Imam Muhammad bin Musa Al-Damiry (D. 808 AH) in Aljarh and Al-Tadeel.He is one of the Shafi’i's Fiqh, through his book "Alnajm Alwahaj" in Sharh Al-Minhaj of Imam Al-Nawawi, which is a foundation in Shafi’i's Fiqh.So I took examples of the hadiths cited by the author, and judged them, to show the extent of applying the rules of Aljarh and Ta'deel with him, and. I divided the subject into three sections, the first section: I took the theoretical foundations of the research, from the definition of Imam Al-Damiri and his book Al-Minhaj, and the research terms, and in the second section: I took the method of EL-Emam Al-Damiry, in Aljarh and Ta'deel. In the third section, I took the terms of doubting and amendment. In the third topic: I studied the terminology of the Aljarh and Ta'deel that Imam Al-Damiry applied to the narrators, then the research concluded the results, the most important of which are the following:1- Imam Al-Damiri’s ways and methods varied in judging the narrators, so sometimes he judges them in all, and sometimes he details on his rulings.2- Imam Al-Dumairi mastered the field of hadeeth sciences in general, and in Al-Jarh and Ta’deel in particular, so he cited the hadith, then judged its narrators, and sometimes mentioned groups of isnad related to names or nicknames, or other things that indicate the breadth of his knowledge and the height of his science plenty.3-The number of narrators that Imam Al-Damiry himself judged is ten narrators, and he agreed with the rulings of the Imams on them in five narrators, and he disagreed with them in the others, and his saying is preferred in what he disagreed with, because some of the narrators were called terms that did not apply to terms, and sometimes they were called general terms that needed elaboration, so he didn't elaborate on them, as is the case in Ibn Luhi'a.
Keywords: method; trust; Straightness; Acceptable; unacceptable